Short-term hydrological forecasts using linear regression / Prévisions hydrologiques à court terme obtenues en utilisant la régression linéaire - Lefebvre, M. (Revue des sciences de l'eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 2003)
A very simple model for the flow of a river, obtained through linear regression, is found to give better results for a certain period when compared to the deterministic model currently in use. The comparisons between the two models are based on three important criteria: the correlation coefficient, the sum of the squares of the errors and the peak criterion. The model examined was used when the river was in spate and the forecasting horizon was a three-day period.